Pengaruh Business Strategy Dan Corporate Social Performance (CSP) Terhadap Return Saham - Indalisti Indalisti; Dirvi Surya Abbas; Dewi Rachmania (Jurnal Kendali Akuntansi, 2024)
The purpose of this study was to determine the effect of business strategy and corporate social performance on stock returns in non- financial companies listed on the Indonesia Stock Exchange (BEI). The research time period used is 5 years, namely the 2015-2019 period.The population of this study includes all non-finance listed on the Indonesia Stock Exchange (BEI) for the 2015-2019 period. The sampling technique was using purposive sampling technique. Based on the predetermined criteria, 136 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. The results showed that corporate social performance has a negative effect on stock returns, while the business strategy have no effect on stock returns. However, simultaneously the, business strategy and corporate social performance affect stock returns.